Maternal Caregiving and Strategies Used by Inexperienced Mothers of Young Infants with Complex Health Conditions. Issue 6 (14th October 2014) - Gardner, Marcia
ABSTRACT Objective To describe maternal caregiving and related strategies used by first‐time mothers of young infants with complex health conditions (CHC) in the first 6 months after discharge. Design Grounded theory. Setting Data were collected in participants' homes in the Northeast United States. Participants Eight first‐time mothers of infants age 6 months or younger with CHC. Methods Purposive and theoretical sampling were used. Semistructured interviews were completed at 2‐month intervals, beginning 2 weeks after their infants' discharge. Analysis of 28 interviews was done with the constant comparative method. Results A grounded theory of maternal caregiving was conceptualized from the data. This time‐and‐experience‐mediated process involved three phases of increasing confidence and expertise, developing in the context of decision‐making responsibility. Related maternal strategies included appraising, normalizing, organizing, assessing, practicing, validating, experimenting, nurturing, and negotiating. Mothering became predictable and integrated in everyday life by about 6 months after the infant's discharge home. Conclusion Findings can help clinicians and researchers better understand what happens over time as new mothers care for infants with CHC. Exploration of these patterns in a more diverse group of mothers of children with CHC can support the development of targeted interventions for this specialized population.